Vicente Risco e a modernidade. Lectura e análise de tres relatos - Sánchez Ferraces, Xosé Luís (Madrygal. Revista de Estudios Gallegos, 2008)
Unsatisfied, discontented with his time, Vicente Risco took part with valor –the same thing other many contemporary writers did- in the assault to the big myths of the XIXth and XXth century: the reason, the science and the progress. To obtain his aim he made use of essays, novels and tales, indistinctly. This work tries to demonstrate that a part of his narrative work, the acting by small stories Do caso que lle aconteceu ó doctor Alveiros, O lobo da xente and A trabe de ouro e a trabe de alquitrán, it was thought and written from a few premises unrationalits in that the dream, the fantasy, the myth, the legend, the tradition, the nature and the instinct were the true exit ramps to the most authentic an real thing.
Keywords: Dissatisfaction; Modernity; Myth; Tradition; Nature